Mosaic loss of non-muscle myosin IIA and IIB is sufficient to induce mammary epithelial proliferation - Georgess, Dan (2017)
The mammary epithelium elaborates through hormonally regulated changes in proliferation, migration and differentiation. Non-muscle myosin II (NMII) functions at the interface between contractility, adhesion and signal transduction. It is therefore a plausible regulator of mammary morphogenesis. We tested the genetic requirement for NMIIA and NMIIB in mammary morphogenesis through deletion of the three NMII heavy chain-encoding genes (NMHCIIA, NMHCIIB and NMHCIIC; also known as MYH9, MYH10 and MYH14, respectively) that confer specificity to the complex. Surprisingly, mosaic loss, but not ubiquitous loss, of NMHCIIA and NMHCIIB induced high levels of proliferation in 3D culture. This phenotype was observed even when cells were cultured in basal medium, which does not support tissue level growth of wild-type epithelium. Mosaic loss of NMIIA and NMIIB combined with FGF signaling to induce hyperplasia. Mosaic analysis revealed that the cells that were null for both NMIIA and NMIIB, as well as wild-type cells, proliferated, indicating that the regulation of proliferation is both cell autonomous and non-autonomous within epithelial tissues. This phenotype appears to be mediated by cell–cell contact, as co-culture did not induce proliferation. Mosaic loss of NMIIA and NMIIB also induced excess proliferation in vivo. Our data therefore reveal a role for NMIIA and NMIIB as negative regulators of proliferation in the mammary epithelium.